Una democratización tambaleante. Escolarización y cohesión social en Chile, 1920-1960 - Rengifo Streeter, Francisca (Universidad Nacional del Litoral, 2019)
This article addresses the relationship between schooling and social cohesion in Chile during the mass schooling process that began with the compulsory school established in 1920. The extensive nature of this process intervened in the socially inclusive sense of education, evidencing the national fracture embodied in thousands of malnourished children. To understand the tensions and mutual transformations between the school as a builder of a common social denominator and the expectations of cohesive inclusion expressed in the democratizing discourse of the period, it analyses the coverage, the desertion and the school assistance policy. The results show that, although several actors diagnosed the physical-cognitive underdevelopment suffered by the child population, the educational policy was unequally inclusive, and it assumed that the social security system would face this problem indirectly.